Observation of Interactions in Adolescent Group Therapy: A Mixed Methods Study - Arias-Pujol, Eulàlia; Anguera, M. Teresa (Frontiers in Psychology, 2017)
Group psychotherapy is a useful clinical practice for adolescents with mental health issues. Groups typically consist of young people of similar ages but with different personalities, and this results in a complex communication network. The goal of group psychoanalytic psychotherapy is to improve participants’ mentalization abilities, facilitating interactions between peers and their therapist in a safe, containing environment. The main aim of this study was to analyze conversation turn-taking between a lead therapist, a co-therapist, and six adolescents over the course of 24 treatment sessions divided into four blocks over 8 months. We employed a mixed-methods design based on systematic observation, which we consider to be a mixed method itself, as the qualitative data collected in the initial observation phase is transformed into quantitative data and subsequently interpreted qualitatively with the aid of clinical vignettes. The observational methodology design was nomothetic, follow-up, and multidimensional. The choice of methodology is justified as we used an ad hoc observation instrument combining a field format and a category system. Interobserver agreement was analyzed quantitatively by Cohen’s kappa using the free QSEQ5 software program. Once we had confirmed the reliability of the data, these were analyzed by polar coordinate analysis, which is a powerful data reduction technique that provides a vector representation of relationships between categories. The results show significant relationships between the therapist and 1) the activation of turn-taking by the participants and the co-therapist and silence and 2) conversation-facilitating interventions and interventions designed to improve mentalization abilities. Detailed analysis of questions demonstrating interest in others showed how the communication changed from radial interactions stemming from the therapist at the beginning of therapy to circular interactions half way through. Repetition was found to be a powerful conversation facilitator. The results also illustrate the role of the therapist, who 1) did not facilitate interventions by all participants equally, 2) encouraged turn-taking from more inhibited members of the group, 3) stimulated conversation from the early stages of therapy, and 4) favored mentalization towards the end. Despite its complexity, polar coordinate analysis produces easy-to-interpret results in the form of vector maps.